Analisis Kemampuan Pemahaman Konsep Siswa Pada Materi Relasi dan Fungsi dengan Pendekatan Teori APOS - Rahman, Muhammad Ridho; Cahayani, Salsabila Widya; Kurniadi, Ellika (Program Studi Pendidikan Matematika FKIP UNIVA Medan, 2025)
This study is a descriptive research with a qualitative approach. The purpose of this research is to describe students' conceptual understanding abilities on the topic of relations and functions using the APOS theory (Action, Process, Object, Schema). The subjects of this research were 32 students from class VIII.6. The study was conducted during the 2024/2025 academic year at SMP Negeri 57 Palembang. Data collection techniques used in this research were written tests and interviews. The data analysis techniques involved analyzing the results of the written tests and interviews. The findings revealed that students' conceptual understanding abilities fell into the medium category, with an average score of 68.75. Students demonstrated varied levels of understanding. Some students correctly solved problems showing they understood the basic rules of relations and functions, but struggled with more complex tasks, such as solving given functions, determining the set of ordered pairs in relations, and defining mappings.